IMPLEMENTASI BIMBINGAN KONSELING DALAM PEMBINAAN AKHLAK PESERTA DIDIK - Ujang Saepul Hamdi (UNISAN JURNAL, 2024)
The point of this exploration is to portray the execution of advising direction in understudy moral preparation, an instructive cycle that spotlights on changing understudies' ethics and conduct so they act well and are moral. The execution of advising direction in fostering the ethics of understudies at Madrasah Ibtidaiyah (MI) An-Najwa Parungkuda Sukabumi West Java has been done well. Direction and Guiding are exercises that can't be isolated. The word Direction is constantly joined with Guiding as a compound word. Advising, which is one of the direction procedures, is frequently supposed to be the center of all administrations and direction. Information assortment strategies were completed utilizing perception, meetings and documentation. In the examination, information decrease steps were done. In the interim, to dissect it utilizing inductive reasoning. In view of the information got, the consequences of examination on the utilization of directing direction in understudies' ethical improvement show a genuinely decent and huge degree of progress, as should be visible from understudies continuously following advising direction and moral advancement utilizing techniques for grasping, counsel, inspiration, proposal and adjustment. So you can gradually change the qualities and propensities for understudies to improve things.